Utilization of a ts-sacB selection system for the generation of a Mycobacterium avium serovar-8 specific glycopeptidolipid allelic exchange mutant - Belisle John T; Inamine Julia M; Eckstein Torsten M; Lee Sun-Hwa; Irani Vida R; Maslow Joel N (BMC, 2004)
Abstract Background Mycobacterium avium are ubiquitous environmental organisms and a cause of disseminated infection in patients with end-stage AIDS. The glycopeptidolipids (GPL) of M. avium are proposed to participate in the pathogenesis of this organism, however, establishment of a clear role for GPL in disease production has been limited by the inability to genetically manipulate M. avium. Methods To be able to study the role of the GPL in M. avium pathogenesis, a ts-sacB selection system, not previously used in M. avium, was employed as a means to achieve homologous recombination for the rhamnosyltransferase (rtfA) gene of a pathogenic serovar 8 strain of M. avium to prevent addition of serovar-specific sugars to rhamnose of the fatty acyl-peptide backbone of GPL. The genotype of the resultant rtfA mutant was confirmed by polymerase chain reaction and southern hybridization. Disruption in the proximal sugar of the haptenic oligosaccharide resulted in the loss of serovar specific GPL with no change in the pattern of non-serovar specific GPL moieties as shown by thin layer chromatography and gas chromatography/mass spectrometry. Complementation of wild type (wt) rtfA in trans through an integrative plasmid restored serovar-8 specific GPL expression identical to wt serovar 8 parent strain. Results In this study, we affirm our results that rtfA encodes an enzyme responsible for the transfer of Rha to 6d-Tal and provide evidence of a second allelic exchange mutagenesis system suitable for M. avium. Conclusion We report the second allelic exchange system for M. avium utilizing ts-sacB as double-negative and xylE as positive counter-selection markers, respectively. This system of allelic exchange would be especially useful for M. avium strains that demonstrate significant isoniazid (INH) resistance despite transformation with katG. Through the construction of mutants in GPL or other mycobacterial components, their roles in M. avium pathogenesis, biosynthesis, or drug resistance can be studied in a consistent manner.